Amplifying Student Learning through Volunteering - McFadden, Amanda; Smeaton, Kathleen (Journal of University Teaching and Learning Practice, 2017)
Student volunteer experiences are ubiquitous within higher education contexts. Despite this, there is further scope for understanding the qualitatively different ways students experience volunteering. To achieve this an explicit focus on understanding volunteer experiences from the students’ perspective and the relationship these experiences have with student learning is vital. This paper used a phenomenographic research approach to present the experiences of seven students involved in an interdisciplinary volunteer program in a community literature festival. The findings revealed experiences ranging from authentic learning to more sophisticated and amplified student experiences. While all students in this study found volunteering to be beneficial, we argue that differentiation of volunteer opportunities for students strengthens the provision for rich student learning through volunteering and the potential for students to be active in social change activities through volunteering.